POST TRAUMATIC STRESS DISORDER (GANGGUAN STRESS PASCA TRAUMA BENCANA) DI JAWA TENGAH - Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Disaster is an event that is not desired, but the perceived intensity increased in recent years. Handling of victims who have not been up demanding attention to the duties and responsibilities of government and society. The research aims to: identify the identification procedure Dissorder Post Traumatic Stress, PTSD sufferers handling as well as efforts to prevent and control the incidence of PTSD in post-disaster in Central Java, to identify the role of government agencies and non-health non-governmental agencies in efforts to address, prevent and control the incidence of PTSD in the area disaster, PTSD develop an integrated management scheme in the affected areas in Central Java. Descriptive qualitative research approach using survey methods, the study site in Karanganyar, Starch, Cilacap, Brebes, Klaten and Banjarnegara. This type of compaction of primary and secondary data, data collection through in-depth interviews and observation of the symptoms or the object under study and interviews with victims.Reality on the ground the team equipped with the knowledge necessary to help victims cope with PTSD when PTSD. The role of non-health government agencies and non-government in the identification, handling is more involved, monitoring and evaluation has not dilakukan.Kebijakan government that governs the role of non-governmental agencies in connection with Standard operating procedures have not been there. The pattern of integrated management of PTSD has not been done. There are no regulations / specific policies of local or central government which regulates the pattern of PTSD post-disaster management in an integrated way. Recommendations are proposed, the need for mental health treatment activity before and after the disaster, develop post-disaster PTSD as a priority program in disaster management by the Central Government, provincial and regency / city an estimated disaster-prone, introducing / socialization PTSD in disaster areas, so that people can recognize the existence of PTSD happens to him, should be piloted handling integrated health center began, the integration of the district in preparation for handling through hospital-based, counseling to Cadre Village/Hamlet confront, prevent PTSD,need community-based treatment patterns,village based alert and soul the hospital.